PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI KECAMATAN CIBADAK KABUPATEN SUKABUMI - irma purnamasari (Universitas Djuanda Bogor, 2011)
The Development which is closing the needs of community is a demand on this autonomy era. However, many obstacles are found in every step of the executions, and one of them is planning. Ideally, the development planning should be participative and have orientation on the basic needs of the community. Sometimes these 2 things are abandoned due to following: (1) Lack of understanding on development planning from community and government officials; (2) The Community sometimes became pessimistic on the development planning as they ideas are difficult to be accommodated when it comes to higher process; (3) The Limitations of government officials and development agents (kader) which duty is to communicate the development planning to the community; (4) The Period of development planning is very short and very imbalance with the materials that need to be discussed and decided.